WDM technologies passive optical components. - Dutta, Achyut K.; Dutta, N. K. (Niloy K.), 1953-; Fujiwara, Masahiko
Internet information (which is doubling every six months) travels through optical fibers. Today's fiber carries information 200 times faster than five years ago, due in large part to technology known as wavelength division multiplexing (WDM). WDM technology relies on the fact that optical fibers can carry many wavelengths of light simultaneously without interaction between each wavelength. As a result, a single fiber can carry many separate signals simultaneously, by sending them along various, different wavelengths carried by the same burst of light. This book will be an excellent resource fo.